2010
DOI: 10.2298/tsci1001183m
|View full text |Cite
|
Sign up to set email alerts
|

Convective cooling of tandem heated triangular cylinders placed in a channel

Abstract: Numerical simulations of forced convective incompressible flow in a horizontal plane channel with adiabatic walls over two isothermal tandem triangular cylinders of equal size are presented to investigate the effect of wall proximity of obstacles, gap space (i.e. gap between two squares), and Reynolds number. Computations have been carried out for Reynolds numbers of (based on triangle width) 100, 250, and 350. Results show that, wall proximity has different effect on first and second triangle in fluid charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 13 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…The results show that when the flow is unsteady, the downstream cylinder experiences very large unsteady forces that may lead to wake-induced flutter. Other papers of flow characteristics about flow over two cylinders in different configurations were published in [4][5][6], and in other studies, that relate to heat transfer and fluid flow over two cylinders can be found in the contemporary literature [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The results show that when the flow is unsteady, the downstream cylinder experiences very large unsteady forces that may lead to wake-induced flutter. Other papers of flow characteristics about flow over two cylinders in different configurations were published in [4][5][6], and in other studies, that relate to heat transfer and fluid flow over two cylinders can be found in the contemporary literature [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%